2021
DOI: 10.3390/socsci10100374
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Practice in the Community—What Does the Community Think?

Abstract: The many changes that occur in the lives of older people put them at an increased risk of being socially isolated and lonely. Intergenerational programs for older adults and young children can potentially address this shortfall, because of the perceived benefit from generations interacting. This study explores whether there is an appetite in the community for intergenerational programs for community dwelling older adults. An online survey was distributed via social media, research team networks, and snowballin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…The research emphasizes that the motivation of older adults is an important factor in promoting PA and intergenerational PA. To attract older adults to participate in intergenerational PA, it is necessary to consider older adults' motivation to participate and its significance, which is consistent with the previous studies [ 27 , 51 , 53 ].…”
Section: Discussionsupporting
confidence: 64%
“…The research emphasizes that the motivation of older adults is an important factor in promoting PA and intergenerational PA. To attract older adults to participate in intergenerational PA, it is necessary to consider older adults' motivation to participate and its significance, which is consistent with the previous studies [ 27 , 51 , 53 ].…”
Section: Discussionsupporting
confidence: 64%
“…Embracing the excitement and opportunity of the GrandSchool vision requires both policy advocacy and community awareness/education around the possibility of intergenerational living and learning. While existing pilots are examining co‐location of early childhood centres and university campuses with residential aged care services, 5,7–10,12–14 research into the co‐location of retirement villages with high school settings remains lacking.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of research has demonstrated that intergenerational programs have positive impacts on physical and mental health, with these programs focused primarily on interactions between older people and younger children (preschool and primary school) 1–8 . There are a number of challenges in implementing such intergenerational initiatives, including: regulatory conflicts; physical environment implications; the logistical challenges of operating educational entities, aged care and/or retirement villages in the one location; the challenge of change and conflicting perspectives on the value, alongside low societal awareness and a paucity of empirical research to support the development of intergenerational learning and care centres 8–10 …”
Section: Introductionmentioning
confidence: 99%
“…We engaged in phenomenological analysis allowing us to gain insights into the perceptions and experiences of the engagements and how meaning was made from the experience (Bennett, Froggett, & Muller, 2019). We observed and made notes, and individually and as a group listened to all recordings, choosing to work with the expressive and nuanced expression available in the audio recording (rather than reverting to transcripts) (Kenning et al, 2021; Froggett & Wengraf, 2004)).…”
Section: The Pre-engagementmentioning
confidence: 99%